Kaidah al-Kitābah ka al-Khiṭāb dan Penerapannya dalam Fikih Muamalah - Askar Patahuddin; Jujuri Perdamaian Dunia; Fatimah Mursyid (AL-KHIYAR: Jurnal Bidang Muamalah dan Ekonomi Islam, 2022)
This study aims to determine the position of the rules of al-Kitᾱbah Ka al-Khiṭᾱb in fiqh muamalah, and to determine the application of the rules of al-Kitbah Ka al-Khib in fiqh muamalah. This study uses a qualitative literature method with deductive data analysis. The research results found are as follows; First; The position of the Rule of Al-Kitābah Ka al-Khiṭāb in Islamic fiqh is the same as the expression/speech. This means that written expressions are the same as verbal expressions, while what is meant in the speech in this discussion is an expression or delivery or something that is conveyed. As well as verbal expression, it is the same as written expression as it is said: "that the pen is one of the two spoken and written for people who are far away the same position as talking to people who are close". As for someone's writing, it can be a reminder/evidence if some of them forget it in the muamalah. Second; The application of the rules of al-Kitᾱbah ka al-Khiṭᾱb in muamalah fiqh such as buying and selling, borrowing, leasing and pawning is prescribed and the law is allowed based on the basis of the rules of al-kitābah ka al khiṭāb from the Qur'an, sunnah, ijma and kiyas.